Complex geophysical research, geostatistical analysis and 3D modeling, with electrical and nuclear methods in Macanal and Chinavita, Boyacá, Colombia - Fonseca-Benítez, Fredy Alexander (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
The implementation of geophysical methods is very important in the realization of projects that permit avaluating us the geological formations geologically-geophysically and specifically units present lithologies in them. From now on the shows the survey area's geologycal frame in which himself i accomplish the methodology of fieldworks and results obtainded as from the implementation of electric method of radiometry. Just the same him self i accomplish an analysis geostatics of data of comparison among population by means of block diagrams of frequencies of physical measured parameters.